MULTICULTURAL-BASED GUIDANCE AND COUNSELING PROGRAM FOR STUDENTS SMP NEGERI 3 SUNGAI RAYA KUBU RAYA REGENCY - Rustam Rustam; Sulha Sulha; Hastiani; Hendra Sulistiawan; Kamaruzzaman Kamaruzzaman (Adisam Publisher, 2025)
Education is expected to direct the community in self-development as a demand of a multicultural society. These efforts can be carried out through the BK program. Research objectives: to produce a multicultural-based BK program. Research design: Research and Development, the research subjects of 77 students were selected by Disporportionate Stratified Random Sampling. Data collection instruments through interviews and scales. Descriptive statistical data analysis. Research results: 1) The program has not touched the need assessment; 2) The program has not involved stakeholders; 3) The implementation of the program has not been in accordance with the plan; 4) Limited infrastructure, manpower, funds. 5) Problems of multicultural attitudes and or behaviors: a) Tolerance and Kinship (20.78%); b) Humanism, Discrimination and Marginalization (19.48%); c) Intercultural Rationality and Prioritizing Common Interests (16.88%); d) Prioritizing Consensus Deliberation (12.99%); e) Equality (10.39%); f) Prioritizing the Integrity of the Nation (9.09%); g) Piety and Maintaining the Balance of Rights and Obligations (7.79%). Conclusion: 1) The BK program in schools already exists, the scope of content only contains services and materials and the number of managers is far from the ideal level. 2) The implementation has not involved stakeholders, need assessment, and is not in accordance with the plan. 3) The preparation of a multicultural-based BK program includes: rationality, vision and mission, definition, objectives, description of needs, components, operational plans, theme development, evaluation. Accommodated in a calendar of activities that have been validated by experts/experts and practitioners through Focus Group Discussion score 67.20.